Психосоматические изменения у пострадавших вследствие чрезвычайной ситуации техногенного происхождения - Onishchenko Н. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The article represents the results of the research of the particularities of impact of a psychological trauma during an emergency on the psychosomatic state of victims. The article also considers main people reactions at the tragedy, studies indices of their functional state and groups of most common health complaints, and determines the levels of psychosomatic disorders at victims of different categories.